A straightforward synthesis of a new family of molecules: 2, 5, 8-trialkoxyheptazines. Application to photoredox catalyzed transformations. Issue 73 (13th August 2020) - Le, Tuan; Galmiche, Laurent; Masson, Géraldine; Allain, Clémence; Audebert, Pierre
Abstract : We have prepared several 2, 5, 8-trialkoxyheptazines starting from the soluble precursor 2, 5, 8-tris(3, 5-diethylpyrazolyl)-heptazine. Abstract : We have prepared several 2, 5, 8-trialkoxyheptazines starting from the soluble precursor 2, 5, 8-tris(3, 5-diethylpyrazolyl)-heptazine. We present their synthesis along with their promising spectroscopic and electrochemical properties, which demonstrate large band gaps and high reduction potentials altogether. Subsequently, we provide a short assessment of the promising ability of one of these molecules to perform catalytic oxidation test-reactions.